New insights into the therapeutic potentials of statins in cancer - Liu, Chengyu; Chen, Hong; Hu, Bicheng; Shi, Jiajian; Chen, Yuchen; Huang, Kun (Frontiers in Pharmacology, 2023)
The widespread clinical use of statins has contributed to significant reductions of cardiovascular morbidity and mortality. Increasing preclinical and epidemiological evidences have revealed that dyslipidemia is an important risk factor for carcinogenesis, invasion and metastasis, and that statins as powerful inhibitor of HMG-CoA reductase can exert prevention and intervention effects on cancers, and promote sensitivity to anti-cancer drugs. The anti-cancer mechanisms of statins include not only inhibition of cholesterol biosynthesis, but also their pleiotropic effects in modulating angiogenesis, apoptosis, autophagy, tumor metastasis, and tumor microenvironment. Moreover, recent clinical studies have provided growing insights into the therapeutic potentials of statins and the feasibility of combining statins with other anti-cancer agents. Here, we provide an updated review on the application potential of statins in cancer prevention and treatment and summarize the underneath mechanisms, with focuses on data from clinical studies.